A mathematical model for the formation of oscillation marks in steelmaking industry - Zambrano Fernández, Marcos (2023)
Oscillation marks are defects found on the surface of the final product in the steelmaking industry. In this research, the temperature of a lubricant known as flux that lies inside of the mould is investigated due to its importance in the formation of the oscillation marks. This temperature that decreases in time is obtained numerically via the finite-volume method by using the Openfoam software.